The Farmer and the Bushman. (1st February 2001) - Read, P.; Wyndham, M.
Abstract : We identify two distinct forms of masculinity, Australian and Cuban. The first is best expressed in the nineteenth century bushman's ballads, which celebrated wandering, mateship, independence of bosses, sardonic acceptance of fate, the absence of women and uninterest in the physical landscape. The values of the Cuban guajiro or rural labourer, expressed in the songs of the first half of the twentieth century, celebrated permanence, individualism, a heroic acceptance of fate, the presence of women and a deep attachment to the physical landscape. The differing physical landscapes, the one arid and unforgiving, the other lush and productive, compounded their British and Spanish cultural origins to create two powerful rhetorics of manhood. Both men and their rhetoric were overtaken, then transformed, by political and environmental developments which were not of their choosing.